Antidepressant-like activity of magnesium in the olfactory bulbectomy model is associated with the AMPA/BDNF pathway - Pochwat, Bartlomiej (Psychopharmacology (Berl), 2014)
RATIONALE: Numerous studies suggest agents that act on glutamatergic transmission as potential antidepressants. Preclinical and clinical evidence suggests that magnesium, an N-methyl-d-aspartate receptor blocker, may be useful in the treatment of depression. OBJECTIVE: The aim of this study was to investigate the effects of magnesium on behavior; protein levels of GluN2A, GluN2B [N-methyl-d-aspartate receptor (NMDAR) subunits], GluA1 [α-amino-3-hydroxy-5 methyl-4-isoxazolepropionic acid (AMPA) subunit], phospho-Ser-831-GluA1 (P-S831), phospho-Ser-845-GluA1 (P-S845), and brain-derived neurotrophic factor (BDNF); and messenger RNA (mRNA) levels of GluN2A and GluN2B in different brain areas in the olfactory bulbectomy (OB) model of depression in rats. METHODS: Magnesium was administered once daily for 14 days at three doses (10, 15, and 20 mg/kg, intraperitoneal) to sham and OB rats. Following treatment, open field and passive avoidance tests were performed in the sham and OB rats. After 24 h, the hippocampus, the prefrontal cortex (PFC), and the amygdala of rats treated with the most active dose (15 mg/kg) were harvested, and the protein and mRNA levels were determined. RESULTS: Chronic administration of magnesium (15 and 20 mg/kg) reduced the number of trials required to learn passive avoidance and reduced the OB-induced hyperactivity. OB increased the P-S845 level in the hippocampus, which was reduced by magnesium treatment. Magnesium significantly increased the levels of BDNF, GluN2B, P-S831, and P-S845 protein (and mRNA) primarily in the PFC and the hippocampus in OB rats. CONCLUSION: For the first time, the present results demonstrate the antidepressant-like activity of magnesium in the OB animal model of depression and indicate the potential involvement of the AMPA/BDNF pathway in this activity.